Theoretical Approaches to Defining the Essence of Entrepreneurship - Yatsevich, Natallia (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2026)
This article discusses and synthesizes various scientific approaches to defining the essence of entrepreneurship and the concept of an entrepreneur as an individual engaged in the entrepreneurial process. Emphasis is placed on the necessity of forming an entrepreneurship paradigm grounded in an interdisciplinary scientific framework.